Coronavirus disease (COVID-19): The need to maintain regular physical activity while taking precautions - Chen, P.; Mao, L.; Nassis, G. P.; Harmer, P.; Ainsworth, B. E.; Li, F. (Journal of Sport and Health Science, 2020)
Given the concerns about the increasing spread of COVID-19, it is imperative that infection control and safety precautions be followed. Home stay is a fundamental safety step that can limit infections from spreading widely. But prolonged home stays can increase behaviors that lead to inactivity and contribute to anxiety and depression, which in turn can lead to a sedentary lifestyle known to result in a range of chronic health conditions.Maintaining regular physical activity and routinely exercising in a safe home environment is an important strategy for healthy living during the coronavirus crisis.